Differences in the values of the Burnout Dimensions on Teachers with and Without Symptoms or Health Problems - Menghi, María Soledad (2019)
The aim of the present study was to observe if there are differences in the level of the burnout dimensions between teachers who have experienced symptoms or health problems in the last year and those who have not  in a sample of 223 teachers working in educational institutions (elementary school level). Participants completed the Maslach Burnout Inventory (MBI) in its teachers’ version, and a sociodemographic survey. A two –independent t test was carried out in order to see if both groups of teachers differed significantly in the values obtained for the MBI dimensions (emotional exhaustion, depersonalization, and lack of personal accomplishment). The results of the t test showed significant differences between the groups of teachers, specifically in the dimensions of emotional exhaustion and depersonalization, showing higher values in the group of teachers who reported suffering from symptoms or health problems in the last 12 months.